Highlights : Collectie Voorlinden. - Swarts, Suzanne; de Vries, Jorien (Wassenaar : Stichting Voorlinden, 2016)
Etel Adnan, Ai Weiwei, Philip Akkerman, Francis Alÿs, Hans Arp, Atelier Van Lieshout, Massimo Bartolini, Hans Op de Beeck, Tjebbe Beekman, Joseph Beuys, Alain Biltereyst, Marinus Boezem, Michaël Borremans, Louise Bourgeois, Marcel Broodthaers, Berlinde De Bruyckere, Daniel Buren, Jean-Marc Bustamante, James Lee Byars, Enrico Castellani, Maurizio Cattelan, Willie Cole, Joseph Cornell, Tony Cragg, Martin Creed, Ian Davenport, Jose Dávila, Tacita Dean, Rineke Dijkstra, Kees van Dongen, Olafur Eliasson, Tracey Emin, Leandro Erlich, Hans-Peter Feldmann, Sylvie Fleury, Tom Friedman, Anya Gallaccio, Leo Gestel, Robert Gober, Daan van Golden, Antony Gormley, Dan Graham, Rodney Graham, Mona Hatoum, Damien Hirst, Roni Horn, Isaac Israëls, Ann Veronica Janssens, Donald Judd, Anish Kapoor, Ellsworth Kelly, Anselm Kiefer, Yves Klein, Imi Knoebel, Pyke Koch, Guillermo Kuitca, Yayoi Kusama, Jim Lambie, Sol LeWitt, Richard Long, René Magritte, Mark Manders, Man Ray, Piero Manzoni, Maha Malluh, Henri Matisse, Mario Merz, Astrid Mingels, Piet Mondriaan, Henry Moore, Giorgio Morandi, Ron Mueck, Juan Muñoz, Ernesto Neto, Erwin Olaf, A.R. Penck, Michelangelo Pistoletto, Robin Rhode, Bridget Riley, Jan Schoonhoven, Richard Serra, Jan Sluijters, Pascale Marthine Tayou, Paul Thek, Robert Therrien, Esther Tielemans, Charley Toorop, James Turrell, Kaari Upson, Edmund De Waal, Matthias Weischer, Rachel Whiteread, Carel Willink and Robert Zandvliet
boek